(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Purpose: The objective of the study was to determine the difference between commercially available Telmisartan sustained release tablets in relation to its quality studies. Methods: Four commercially available telmisartan sustain release tablets manufactured in India were evaluated for four in vitro parameters, both official and non-official, viz., uniformity of weight, hardness test, drug content, disintegration and dissolution test. The test was followed as per I.P guidelines Results: All the products met the requirements as per general specifications of Indian Pharmacopoeia for tablets. It is concluded that despite some apparent minor difference in tablet hardness, thickness, drug content and dissolution characteristic of various commercially available Telmisartan sustain release marketed tablets appear to be similar and not significantly different from various manufacturers.